Manfaat, Tantangan, Dampak Sistem Perencanaan Sumberdaya Perusahaan Dalam Organisasi: Tinjauan Literatur Sitematis - Sanjaya, Daniel Robi; Febriandi, Agistra; Widodo, Aris Puji (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Enterprise Resource Planning (ERP) systems provide extensive benefits, challenges, and impacts to the entire enterprise. ERP systems help companies to share and transfer data and information across functional units within and outside the company aiming to achieve different goals. One such aspect is the investment in ERP system implementation. ERP systems collect, record, integrate, manage, and transmit data and information across functional units of the company. In this paper, we follow the Systematic Literature Review (SLR) research method to explore the benefits, challenges, and impacts of ERP system implementation with a literature review conducted using the methodology guide from Kitchenham et al. This method conducts a systematic review consisting of three stages: planning, implementation, and reporting. The conclusion in this study is that there are benefits, challenges and impacts in an integrated ERP system to improve processes and product quality, reduce production cycle time, and improve the decision-making process then there are challenges of security risks and functionality limitations and there are impacts such as reducing time when processing data, increasing efficiency when used and providing high-quality services.